Online Quizzes as a Formative Assessment Tool to Improve Students’ Grammar Learning within a Blended Learning Context - Kihal , Maissoune; Boudehane , Nora (Journal of Human Sciences, 2023)
Recent trends in foreign language assessment have integrated online modes of evaluation: formative and summative.  The former has been used to support the students’ self-directed learning as well as to aid instructors reflect on their teaching practices. This study aims at investigating the effectiveness of utilizing online quizzes as a formative assessment tool to promote sophomores’ grammar learning. In an attempt to achieve the research aim, an experiment has been conducted in which the experimental group received online grammar quizzes whereas the students of the control group did not. Eventually, both groups received the same grammar in-class post-test. After comparing the two groups’ post-test results, the experimental group indicated a difference in the scores obtained in comparison to that of the control group. Such results show that employing online formative assessment in a form of quizzes has improved the students’ grammar learning in a blended learning context.